LITERACY: WHY DO NOT CHILDREN LEARN TO READ AND WRITE? - Mendonca, Onaide Schwartz [UNESP]; Roberto de Oliveira Kodama, Katia Maria [UNESP] (Univ Estadual Paulista-unesp, Fac Ciencias Letras Assis, 2016)
Aiming to investigate whether PNAIC / Literacy allow changes in the Brazilian literacy scenario in the light of Linguistics, we intend to present part of a research that analyzed the units for the first cycle of Basic Education. The results show that, although the theoretical reference is representative and recognize that the systematic teaching of specific content of language is essential for the child to learn, does not propose any methodology and recommended strategies only approach literacy. In order to show that when it teaches the child learns, this text presents results of an Extension Project developed in a Municipal Elementary School (Cycle I) of Presidente Prudente, SP. It is an institution with a history of school failure, where only 55% of students concluded the 5th. year in alphabetic level. After effective teaching values and linguistic content with appropriate methodology, the school had its reality transformed not only at the level of learning, but cordiality and joy. Periodic literacy assessments showed the development of children, because the 1st and 2nd years started 2015 with only 9.3% of children in alphabetic level and concluded with 79% literate. The classes of 3rd, 4th and 5th years concluded 2015 with 93.7% of children fully literate.
Keywords: Literacy; Systematic teaching; Significant learning